ROLES OF HIGHER EDUCATION INSTITUTIONS (HEIS) IN PRODUCING HOLISTIC GRADUATES - Eshaby Mustafa; Nurhazlina Mohd Ariffin; â€˜Ain Husna Mohd Arshad; Ani Munirah Mohamad; Nur Aili Hanim Hanafiah (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2024)
Higher education institutions (HEIs) largely aim to produce holistic graduates, best in both worlds of academic and non-academic aspects. Although numerous literatures have identified and described â€œholistic educationâ€, it remains an issue if the students actually understand and appreciate the said term. Accordingly, this study seeks to investigate the studentsâ€™ perception of HEIâ€™s role of producing holistic graduates. Therefore, this paper seeks to answer two research questions, firstly, what are the characteristics of holistic graduates? And secondly, how do students perceive the academic and non-academic programs at the HEIs towards producing holistic graduates? Engaging in mixed approaches of quantitative and qualitative, this study investigates the studentsâ€™ perception of HEIâ€™s role of producing holistic graduates. An online survey was administered on 357 students of a targeted HEI. The findings reveal that majority of the students are satisfied with the academic and non-academic programs offered at the HEI, as well as their perceived concept of the â€œholistic graduateâ€ itself. Hopefully, the paper would shed light onto further research in the area of studentsâ€™ education and higher learning education generally.